Productive potential and quality of the chipile Crotalaria longirostrata Hook. & Arn. as forage for small ruminants - Aniano-Aguirre, Herminio; Matías-Pérez, Diana; Pérez-Santiago, Alma Dolores; Sánchez-Medina, Marco Antonio; Rojas-García, Adelaido Rafael; Maldonado-Peralta, María de los Ángeles; Chávez-Montaño, Aurora; Antonio-Cruz, Alma Lilia; García-Montalvo, Iván Antonio (Frontiers in Agronomy, 2025)
This study aimed to evaluate the biomass yield and crude protein content of C. longirostrata under different cutting frequencies and intensities, to assess its potential as forage for small ruminants on the coast of Oaxaca, Mexico. Twelve treatments were carried out with three replications, which included three cutting frequencies (35, 70, and 105 days) and four cutting intensities (5, 10, 15, and 20 cm), distributed in randomized complete blocks during the rainy and dry seasons. Variables such as dry matter (DM) yield of total biomass (TB), leaves, stems, and crude protein (CP) in leaves and stems were measured. The highest TB productions were recorded at the frequencies of 70 and 105 days in both periods, and the lowest at the frequency of 35 days; the highest leaf yields occurred at 70 days in rain and at 35 days in dry conditions; for stems, the highest value was observed at 105 days in rain and at 70 days in dry season. The CP was higher in the dry season (37%) in leaves compared to the rainy season and (14%) in stems. It is concluded that we results indicate that C. longirostrata can contribute to diversified and protein-rich forage resources in smallholder systems under tropical conditions.